Description of a new species of the genus \(Hyperaxis\) Germminger & Harold, 1874 (Coleoptera: Chrysomelidae: Eumolpinae) from vietnam with an update key to species - Dinh, Nguyen Thi (Academia Journal of Biology, 2022)
A new species Hyperaxis phuquocnia sp. nov. is described and illustrated from Phu Quoc National Park, Kien Giang province, southern Vietnam based on female specimens. Color photos of habitats and genitalia, and DNA Barcoding data of the new species are presented. An updated key to all species of the genus Hyperaxis in Vietnam is provided.